Internasional Saya Development Of Interactive Learning Media On Renewable Energy Microgrids For Vocational Education Students - Andita; Nurhasana; Sulfitri (Journal of Global Educational Perspectives, 2026)
The rapid development of renewable energy technologies requires vocational education institutions to equip students with relevant knowledge and technical skills, particularly in understanding complex systems such as microgrids. However, conventional teaching methods often fail to effectively convey these concepts due to limited visualization and interactivity. This study aims to develop and evaluate an interactive learning media on renewable energy microgrids for vocational education students. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The developed media integrates simulations, animations, and interactive features to enhance students’ learning experiences. Expert validation results indicated that the media is highly feasible in terms of content accuracy, instructional design, and technical quality. The implementation was conducted using a quasi-experimental design with pre-test and post-test measures. The findings revealed a significant improvement in students’ learning outcomes, supported by a medium-to-high N-Gain score. Additionally, students showed positive responses in terms of engagement and motivation. Despite some limitations related to usability and technical constraints, the developed media proved to be effective in supporting the teaching and learning of renewable energy microgrids. This study contributes to the advancement of interactive learning in vocational education and provides a practical tool for enhancing students’ competencies in the renewable energy sector.